The Neapolitan banks in the context of early modern public banks - François R. Velde (Federal Reserve Bank of Chicago, 2018)
I examine the Neapolitan public banks, a group of non-profit institutions that emerged in the late sixteenth century, in the context of the early public banks that existed elsewhere in early modern Europe. In terms of size and stability they compare well with their peers, in spite of a difficult political and economic environment. They were also remarkably financially advanced for their time. Their success is likely due to their ownership structure, governance, and well managed relationship with the monarchical authorities.
Keywords: E58; N13; 330; central banking; public banks; Naples